Characterization of Subtype Selective Cannabinoid CB2 Receptor Agonists as Potential Anti-Inflammatory Agents - Yaliang Tang; Barbara Wolk; Ryan Nolan; Caitlin E. Scott; Debra A. Kendall (MDPI AG, 2021)
Activation of the CB2 receptor has been shown to have anti-inflammatory and antinociceptive effects without causing psychoactive effects. Previously, we reported that the compound ethyl 2(2-(N-(2,3-dimethylphenyl) phenylsulfonamido)acetamido)benzoate (ABK5) is a CB2 subtype selective agonist with anti-inflammatory and antinociceptive effects. In the present study, we tested four ABK5 derivatives, ABK5-1, ABK5-2, ABK5-5, and ABK5-6, to analyze the structure of ABK5 to obtain CB2-selective agonists with higher affinity and efficacy. Affinity, subtype selectivity, and G-protein coupling were determined by radioligand binding assays. Selected compounds were then subjected to evaluation of anti-inflammatory effects using two different cell lines, Jurkat (ABK5-1 and 5-2) and BV-2 cells (ABK5-1), which are models of T cells and microglia, respectively. ABK5-1, ABK5-2, and ABK5-6 had comparable CB2 binding affinity with ABK5 (and stimulated G-protein coupling), while only ABK5-1 and ABK5-2 maintained CB2-subtype selectivity. ABK5-5 did not bind CB2 in the detectable range. RT-PCR and ELISA analysis showed that the two compounds also inhibit IL-2 and TNF-α production, and they were more efficacious than ABK5 in inhibiting TNF-α production. CXCL-12 mediated chemotaxis was also evaluated by the transwell migration assay, and both ABK5-1 and ABK5-2 inhibited chemotaxis with a stronger effect observed in ABK5-1. In the microglia cell line BV-2, ABK5-1 inhibited IL-1β and IL-6 production, which suggests this compound has anti-inflammatory effects through targeting multiple immune cells, and may be a candidate for treatment of inflammation.